Magic in the Modern World : Strategies of Repression and Legitimization - Styers, Randall; Bever, Edward (Book collections on Project MUSE., 2017)
"A collection of essays on various aspects of the position of magic in the modern world. Essays explore the ways in which modernity has been defined in explicit opposition to magic and superstition, and the ways in which modern proponents of magic have worked to legitimate their practices"--Provided by publisher